Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0309364611423130
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the pistoning measurement in transtibial prosthesis

Abstract: Background: Good suspension lessens the pistoning (vertical displacement) of the residual limb inside the prosthetic socket. Several methods are used for measuring the pistoning.Study Design: Clinical trial.Objectives: To introduce and evaluate a new simple method for measuring the pistoning between the soft liner and socket in transtibial prostheses.Methods: Five transtibial prostheses with Iceross silicone liner and shuttle lock were made for the subjects. The pistoning was measured between the liner and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 23 publications
3
48
0
Order By: Relevance
“…Comparing our results with those of Gholizadeh et al using the same PT methodology, we found that the displacement observed in the 0 N and 30 N condition with a shuttle lock system (10 ± 9.2 mm and 14 mm, respectively) was more than that obtained in our study with the SSS (7.5 ± 4.7 mm and 12.4 ± 5.6 mm). 12 Klute et al 13 reported similar results in pin lock suspension pistoning at 0 N (6 ± 4 mm). To our knowledge, there are no studies comparing ECW with two different suspension systems in the recent literature.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Comparing our results with those of Gholizadeh et al using the same PT methodology, we found that the displacement observed in the 0 N and 30 N condition with a shuttle lock system (10 ± 9.2 mm and 14 mm, respectively) was more than that obtained in our study with the SSS (7.5 ± 4.7 mm and 12.4 ± 5.6 mm). 12 Klute et al 13 reported similar results in pin lock suspension pistoning at 0 N (6 ± 4 mm). To our knowledge, there are no studies comparing ECW with two different suspension systems in the recent literature.…”
Section: Discussionmentioning
confidence: 69%
“…The importance of a proper suspension system to guarantee amputees' comfort and prosthetic function has been widely indicated in the literature, and vertical displacement or pistoning within the socket has been suggested to be one of the main indicators of suspension system efficacy in lower-limb prostheses. 1,4,12,14,30 We found a Table 3. TUGT, HSQ, and LCI results (mean ± SD).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…32 Recently, a simple photographic method has been reported 29,36-37 and finally, Gholizadeh et al 38 used Vicon motion analysis system to evaluate pistoning in transtibial amputees. The literature review revealed that the majority of researchers measured the displacement between the bone and the socket, the liner and socket or the soft tissue, by using different techniques in static position 19,29,32,[34][35][36][37][38]53,55 or during dynamic tasks 33,35,54,[60][61] to check pistoning inside the socket. Therefore, the methods available were classified according to whether they utilized static or dynamic pistoning.…”
Section: Pistoning Measurement Methodsmentioning
confidence: 99%
“…36 Another study using same photographic methodology revealed that adding loads to the prosthesis caused less pistoning between Seal-In ® X5 liner and the socket (2 mm) compared with Dermo ® liner (4 mm). 29 Gholizadeh et al 38 compared the pistoning between two different transtibial liners (Seal-In ® X5 and Dermo ® liner) and the socket through the use of a motion analysis system. The analysis of the data showed the maximum amount of pistoning within the socket occurred after 90 N was added to the prosthetic limb.…”
Section: Amount Of Pistoningmentioning
confidence: 99%